Application of flocculation combined with vacuum preloading to reduce river-dredged sludge. Issue 2 (7th February 2020) - Liu, Feiyu; Wu, Wenqing; Fu, Hongtao; Wang, Jun; Hai, Jun; Cai, Yuanqiang; Hu, Xiuqing; Yuan, Wenxi; Lou, Xiaoming
Abstract: To achieve the rapid dewatering of dredged sludge, the flocculation–vacuum-preloading method was tested indoors. In this study, the optimal mixing ratio of six flocculants was determined through the settling column test, and then the proposed method was tested. The water drainage and settlement were monitored during the test, while the soil moisture content and shear strength were measured after the test. The results show that all the flocculants had an optimal mixing ratio, and the addition of 0.8% FeCl3 or 0.08% anionic polyacrylamide (APAM) in the sludge can better accelerate solid–liquid separation of the sludge. After the test, the water content in the sludge decreased from 140% to 60%. Compared with general vacuum preloading, the use of the proposed method increased the water drainage by 46.5% and 56.8% and decreased the soil volumes by 60.5% and 82.4% for FeCl3 and APAM, respectively. Moreover, the corresponding shear strength was increased from 10 to 14 and 17 kPa. In addition, the use of APAM increased the solidification rate of heavy metals in the sludge to more than 80%, effectively inhibiting the migration of heavy metals.